Magnesium Supplementation and Blood Pressure in Pregnancy: A Double-Blind Randomized Multicenter Study - Maria Bullarbo; Helena Mattson; Anna-Karin Broman; Natalia Ödman; Thorkild F. Nielsen (Journal of Pregnancy)
Objective. To investigate the effect of magnesium (Mg) supplementation in healthy pregnant women for prevention of blood pressure increase. Secondary outcomes were comparison of biomarkers for hypertensive disorders and labour and fetal outcomes between the groups. Methods. Two hundred nulliparous healthy pregnant women were double-blind randomized to receive Mg daily or placebo. Results. There were no differences in blood pressure increase. However, among the Mg-treated women, there was a significant negative correlation between increase in blood levels of magnesium and increase in systolic blood pressure (p = 0.042). Magnesium supplementation seems to be safe for both mother and infant. Conclusion. Magnesium supplementation in healthy first-time pregnant women is not to be recommended for prevention of blood pressure increase. Supplementation in risk pregnancies needs to be further investigated. The study is listed on the ISRCTN registry with study ID 13890849.